Midwifery Care for Third Trimester Pregnant Women with Frequent Urination in Clinics and Maternity Homes: Asuhan Kebidanan Ibu Hamil Trimester III Dengan Sering Buang Air Kecil Di Klinik dan Rumah Bersalin - Welerubun, Talitha Zain; Rusdyati, Tutik; Azizah, Nurul (Universitas Muhammadiyah Sidoarjo, 2020)
Pregnancy is the union of spermatozoa and ovum and is continued by nidation or implantation. Pregnancy occurs for 40 weeks divided into 3 trimesters, namely in the first trimester occurring at 1 -13 weeks of gestation, the second trimester at 14-26 weeks of gestation and the third trimester at 27-40 weeks of gestation. In the third trimester of pregnancy there are several complaints including: edema, frequent urination, itching and stiffness in the fingers, bleeding gums, hemorrhoids, difficulty sleeping, vaginal discharge, increased sweating, constipation, leg cramps, numbness and pain in the feet and hands, shortness of breath, round ligament pain, palpitations, heartburn, flatulence, ptyalism, dizziness, headache, backache, and varicose veins in the legs or vulva. Frequent urination occurs due to the enlargement of the uterus which can cause the lower part of the fetus to descend which can put pressure on the bladder.